Agricultural Land Product-Sharing Transactions in the Local Community of the Besemah Tribe - Herawan Sauni; Putra Perdana Ahmad Saifulloh; Sonia Ivana Barus; Akhmad Akhmad; Asrul Ibrahim Nur (Khazanah Hukum, 2026)
This study aims to determine the pattern of transactions for the results of agricultural land in the local community of the Besemah tribe. By using explorative juridical methods, and empirical legal research, as well as functional interpretation, it can be concluded that: 1. In order to fulfill the need for resources (land) for agricultural land (paddy fields or farm) in the Besemah community, it is carried out using various models. The models are nyaseh, surungan, tempohan, paruan, and sande. 2. The existence of profit-sharing legal institutions (nyaseh, surungan, tempohan,paruan, and sande) are still in force in the besemah tribal community. 3. The legal institutions for the sharing of agricultural land (nyaseh, surungan, tempohan,paruan, and sande) are not solely oriented towards economic aspects, but what really stands out are the aspects of mutual help and kinship. 4. In essence, Nyaseh, Surungan, Tempohan, Paruan, and Sande are agricultural land production sharing agreements with models that vary widely according to the nature and allotment of the land (right to use) itself. 5. In the transaction for the results of agricultural land (nyaseh, surungan, tempohan,paruan, and sande) in practice there are no formalities as stipulated in the law. For the semah community, the existence of these formalities will actually lead to rigidity, and eliminate the philosophy of the existence of these legal institutions.